Notary Authority in Certifying Electronic Transaction Documents - PRABHAWISNU, Anak Agung Gede Krisna; SUJANA, I Nyoman; WESNA, Putu Ayu Sriasih (Indonesia Strategic Sustainability, 2023)
Purpose:Electronic transaction certification is another form of authority a notary possesses, and more study still needs to be done on this matter. Hence, this research attempts to examine this matter in more depth. The rapid development of technology has given birth to convenience for human life, including in law, especially notaries. The existence of a cyber notary formulated in Article 15 paragraph (3) of the Notary Office Law gives a notary the authority to certify transactions electronically.Methodology:The method chosen for this research is normative legal research by analyzing and interpreting legal and social facts.Findings:This authority still needs clear guidelines, so it is necessary to have a formulation regarding its regulation.Implication:Based on the theory of authority, a notary has the right to certify transactions electronically which is included in attributive authority and is a derivative of the law. It is appropriate that the authority to certify electronic transactions is further regulated so that later it will facilitate the work of notaries and follow utilitarian theory, where good law can provide the broadest possible benefits for society.